(untitled) (Third Sector Social Economic Review, 2022)
During the pandemic, if the current passenger psychological atmosphere is exacerbated by some elements such as negative electronic word of mouth, it might lead to disruptive decisions taken by air travelers. Therefore, the main purpose of this study is to determine whether the mediating role of risk-taking between Covid-19 threat and willingness to fly also is to determine whether moderating role of negative electronic word of mouth between Covid.19 threat and travel attitude after the pandemic. The research was performed by an online survey method consisting of five Likert types scales. These are Covid-19 threat, risk-taking, willingness to fly, negative electronic word of mouth, and travel attitude scales after the pandemic. At the first stage to analyze model hypotheses exploratory factor analysis, reliability analysis, confirmatory factor analysis, and path analyses were performed. At the second stage to evaluate mediating and moderating effects of variables Spss’s process macro bootstrap technic employed which was accepted as a more reliable technic. As a result, all hypotheses were supported in the model. It was significantly found that while risk-taking has a mediating role between Covid-19 threat and willingness to fly, simultaneously, it was found that negative electronic word of mouth has an important moderating role between Covid-19 threat and willingness to fly. Also, it was determined that negative electronic word of mouth significantly affects the Covid-19 threat. Marketing communication and programs need to be challenged by manipulated negative e-Wom in social media for managing the firm’s reputation and consumer perceptions. In contrast, if marketers are able to create a more reliable atmosphere for consumers, it will result in risk-taking behaviour that stimulates positive purchasing decisions for buying air tickets.